Charge-dependent pair correlations relative to a third particle in p+Au and d+Au collisions at RHIC - Adam, Jaroslav; Deppner, Ingo Martin; Herrmann, Norbert (Physics letters, 2019)
Quark interactions with topological gluon configurations can induce chirality imbalance and local parity violation in quantum chromodynamics. This can lead to electric charge separation along the strong magnetic field in relativistic heavy-ion collisions - the chiral magnetic effect (CME). We report measurements by the STAR collaboration of a CME-sensitive observable in p+Au and d+Au collisions at 200 GeV, where the CME is not expected, using charge-dependent pair correlations relative to a third particle. We observe strong charge-dependent correlations similar to those measured in heavy-ion collisions. This bears important implications for the interpretation of the heavy-ion data.
Gesehen am 12.05.2020